Designing a Booth Tenant Reservation System for Cresindo Organizer with a Greedy Algorithm Approach - Muhammad Faqih Maulana Komari; Ginanjar Wiro Sasmito; M. Nishom (Journal of Applied Informatics Science, 2025)
Booking Booth Tenant is an integrated information system developed to address the inefficiencies and allocation errors often encountered in the manual booth reservation process at events organized by Cresindo Event Organizer. This study aims to design and develop a web-based application that facilitates digital and automated booth reservations. The system was developed using the waterfall software engineering approach, with the Greedy algorithm implemented as the core method for allocating booths based on booking order, availability, and strategic location preferences. The results show that the system significantly accelerates the reservation process, improves the accuracy of booth placement, and provides users with an interactive experience through an intuitive booth map interface. In conclusion, the application of the Greedy algorithm in the Booking Booth Tenant system proves effective in enhancing efficiency, transparency, and the overall quality of service provided by Cresindo Event Organizer to its tenants.